Reduced maximal range of ocular movements and its response to acute levodopa challenge in Parkinson's disease - Li, Juan; Li, Yuewen; Chu, Xianzhou; Jiang, Mengxue; Wu, Tieyu; Chen, Xianwen (Frontiers in Aging Neuroscience, 2024)
Introduction: Although restriction of vertical ocular range of motion is known to be the hallmark of progressive supranuclear palsy (PSP), the maximal amplitude of ocular movement has not been quantitatively assessed despite of accumulating evidences of oculomotor dysfunction in Parkinson’s disease (PD). Here, we evaluated the maximal oculomotor range and its response to levodopa in PD, and compare findings to atypical parkinsonism. Methods: We recruited 159 healthy controls (HC) as well as 154 PD, 30 PSP and 16 multiple system atrophy (MSA) patients. Oculomotor range was assessed using a kinetic perimeter-adapted device for the vertical and horizontal axes (four positions). Parameters were reassessed after levodopa challenge and compared among PD, PSP and MSA patients. Results: Maximum oculomotor range in PD patients was reduced as compared to HC. Levodopa improved oculomotor range in all directions; corrective effects of upward range positively correlated with improvements in Unified Parkinson's Disease Rating Scale III and bradykinesia sub-scores among PD patients. Although oculomotor range was markedly restricted among PSP and MSA patients, the beneficial effects of levodopa was less pronounced. Reduced oculomotor range of motion was more significant among PSP as compared to PD or MSA patients; MSA patients did not significantly differ from PD patients. The range of upward gaze was optimally sensitive for differentiating among PD, PSP and MSA patients. Conclusion: Maximum oculomotor range was reduced among PD patients significantly improved by levodopa treatment. Variations in, as well as the positively effects of levodopa on, the range of upward gaze assist diagnostic differentiation among PD, PSP and MSA patients.